2012
DOI: 10.1007/s00203-012-0827-9
|View full text |Cite
|
Sign up to set email alerts
|

ABC transporter genes from Streptomyces ghanaensis moenomycin biosynthetic gene cluster: roles in antibiotic production and export

Abstract: Streptomyces ghanaensis ATCC14672 produces antibiotic moenomycin A (MmA), which possesses strong antibacterial activity. The genetic control of MmA biosynthesis has been recently elucidated; nevertheless, little is known about the roles of two pairs of genes, moeX5-moeP5 and moeD5-moeJ5, coding for ATP-dependent transporter systems. Here we report that both gene pairs form transcriptional units actively expressed during MmA production phase. S. ghanaensis mutants deficient in either (one) or both transporter s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 31 publications
(38 reference statements)
0
13
0
Order By: Relevance
“…One effective way is to pump the antibiotic out of the cells. This process requires the participation of transporters encoded in the antibiotic biosynthetic gene clusters (29,30). Since the biosynthesis of antibiotics is subject to complex cascade regulation, it is reasonable to expect that the export process is also under the control of regulators.…”
Section: Discussionmentioning
confidence: 99%
“…One effective way is to pump the antibiotic out of the cells. This process requires the participation of transporters encoded in the antibiotic biosynthetic gene clusters (29,30). Since the biosynthesis of antibiotics is subject to complex cascade regulation, it is reasonable to expect that the export process is also under the control of regulators.…”
Section: Discussionmentioning
confidence: 99%
“…All constructs were transferred into Streptomyces conjugally. The presence and stability of inheritance of φ C31-based constructs in streptomycetes was checked as described earlier [63,64]. …”
Section: Methodsmentioning
confidence: 99%
“…Notably, among the cellenvelope-active agents tested, moenomycin A was consistently affected by abcA expression, whereas ␤-lactams were variably affected in MSSA and MRSA backgrounds. Moenomycin A, which is a natural hydrophobic antibiotic that inhibits the glycosyltransferase domain of penicillin-binding proteins (PBPs) (41), is known to be a substrate of ATP-dependent transporters in other species. In Streptomyces ghanaensis, the genes moeD5moeJ5 and moeX5moeP5, which are highly similar to abc transporter genes, are involved in the export of moenomycin A (41).…”
Section: Discussionmentioning
confidence: 99%
“…Moenomycin A, which is a natural hydrophobic antibiotic that inhibits the glycosyltransferase domain of penicillin-binding proteins (PBPs) (41), is known to be a substrate of ATP-dependent transporters in other species. In Streptomyces ghanaensis, the genes moeD5moeJ5 and moeX5moeP5, which are highly similar to abc transporter genes, are involved in the export of moenomycin A (41). We have now shown that in an MSSA background there is a 100-fold increase in the MIC of moenomycin A with overexpression of abcA and a 10-fold effect in the MRSA background.…”
Section: Discussionmentioning
confidence: 99%